Assistance with Business License Number Registration for Potential Village SME to Upgrade - Sugiartiningsih Sugiartiningsih; Rizky Dwi Larasati; Suparjiman Suparjiman; Arief Yunan; Saepul Adnan; Abin Suarsa; Erfan Erfiansyah; Eni Kusumawati; Reren Supriatna; Khaerani Arum Kanti; Hilmiah Anandari Ladysta (Universitas Muhammadiyah Palembang, 2024)
Micro businesses, which are the backbone of the Indonesian economy, must be legalized so that they move up a class in improving the economic welfare of the people. To make this happen, government leadership through the empowerment function by creating PIRT for Micro Enterprises. As an initial stage, Micro Businesses must register their Business Identification Number (NIB) to increase consumer confidence and facilitate business transactions. The aim of PkM is to increase the legality of Micro Businesses in Rancatungku village in the culinary, grocery and service sectors through assistance with NIB registration. The PkM implementation method is a lecture to refresh partners about the benefits of NIB in capital, legal strength, increased production and marketing. Meanwhile, for assistance with NIB registration via Online Single Submissions (OSS), a question and answer method is used which is guided by the head of the UMBandung IPR Study Center and accompanied by the PkM head, students and village government representatives through good collaboration by dividing tasks and providing supporting infrastructure for laptops, cellphones and printers. The results of the assistance have resulted in the successful issuance of four NIB certificates for Micro Business actors in the culinary and grocery sectors. It is hoped that having an NIB certificate will motivate them to move up to a higher level in the trade and entrepreneurship sectors. The ease of implementing OSS in licensing services has encouraged other sectors such as BUMDES and student businesses to be registered with NIB.